Impact upon clinical outcomes of translation of PNA FISH-generated laboratory data from the clinical microbiology bench to bedside in real time - Tam Ly; Jyoti Gulia; Vasilios Pyrgos; Masashi Waga; Shmuel Shoham (Dove Medical Press, 2008)
Tam Ly, Jyoti Gulia, Vasilios Pyrgos, Masashi Waga, Shmuel ShohamSection of Infectious Diseases, Washington Hospital Center, Washington DC, USAAbstract: Fluorescence in situ hybridization using peptide nucleic acid probes (PNA-FISH) differentiates Staphylococcus aureus from other Gram-positive-cocci in clusters (GPCC). 101/202 patients with GPCC+ blood cultures were randomly assigned to clinician-notification of PNA FISH results. Notifi cation was associated with reduced mortality (8% vs.17%, p = 0.05), further antibiotic use (median −2.5 days, p = 0.01), and trended toward reduced hospital stay and charges.